Efficacy of transoral incisionless fundoplication for refractory gastroesophageal reflux disease: a systematic review and meta-analysis - McCarty, Thomas R.; Itidiare, Michael; Njei, Basile; Rustagi, Tarun (Endoscopy, 2018)
Background Given poor symptomatic response rates and rising awareness of the adverse events associated with the long-term use of proton pump inhibitors (PPIs), endoscopic modalities for treatment of refractory gastroesophageal reflux disease (GERD) have become more prominent. The aim of this study was to perform a systematic review and meta-analysis to evaluate feasibility, efficacy, and tolerability of transoral incisionless fundoplication (TIF) for the treatment of refractory GERD.Methods Searches of PubMed, EMBASE, Web of Science, and Cochrane Library databases were performed to March 2017. Measured outcomes included immediate technical success rate and serious adverse events. Symptomatic improvement was measured using GERD Health-related Quality of Life (HRQL), Gastroesophageal Reflux Symptom Score (GERSS), and Reflux Symptom Index (RSI). Objective success was determined by hiatal hernia reduction and pH monitoring.Results 32 studies (1475 patients; 48.2 % male) met inclusion criteria. TIF success rate was 99 % (95 % confidence interval [CI] 97 to 100; P < 0.001), with an adverse event rate of 2 % (95 %CI 1 to 3; P < 0.001). GERD HRQL, GERSS, and RSI improved significantly post-TIF (mean difference 17.72, 95 %CI 17.31 to 18.14; mean difference 23.78, 95 %CI 22.96 to 24.60; mean difference 14.28, 95 %CI 13.56 to 15.01; all P < 0.001, respectively). Hernia reduction occurred in 91 % of patients (95 %CI 83 to 98; P < 0.001). DeMeester scores improved significantly (mean difference 10.22, 95 %CI 8.38 to 12.12; P < 0.001). PPI therapy was discontinued post-procedure in 89 % of patients (95 %CI 82 to 95; P < 0.001). Conclusions TIF appears to be a safe and effective endoscopic procedure for patients with refractory GERD. Future controlled trials are needed to directly compare efficacy, long-term durability, and safety between TIF and Nissen fundoplication.